Introduction to transition space in contemporary Iranian housing typology - Mohsen Asadi; Mazlan Mohd Tahir; M.M.Shabani; H. Arjmandi (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2015)
Iranian Islamic traditional houses have changed fast in recent decades. These changes put influence on social life and architecture in the traditional housing plan. For instance, internal architecture of an Iranian house included a courtyard surrounded by rooms and transition spaces for control in privacy, movement and separating people in different situations, but in contemporary housing this cultural element is lost. This paper arguments the quality of changes and stresses the importance of suitability between culture and transition space of the housing plan in Iranian Islamic culture and architecture. Iranian traditional housing plans depended on climate and reflected the culture, people’s beliefs and religion; also, the plans had harmony in lifestyle and the relationship between the spaces of a house. In the contemporary designs of house plans, the transition spaces omit attention to culture and residents’ habits more times than not. The new apartments have many cultural limitations for the relationships of residents. This paper concludes that there is a connection between culture, inhabitants and their beliefs, and the kinds of houses designed (architecture) that the Islamic culture and architecture aim to revive for the future. It also hopes it can have some influence on the large world of Islamic culture, be it the smallest influence.